1991
DOI: 10.1002/mrc.1260291016
|View full text |Cite
|
Sign up to set email alerts
|

Homonuclear scalar 6Li6Li spin–spin coupling: First direct observation and detection via the 6Li,6Li INADEQUATE experiment,

Abstract: A homonuclear 6Li,6Li spin-spin coupling has been directly measured in the case of the dimer of (E)-2-lithio-1-phenyl-1-o-lithiophenylpent-1-ene. This constitutes the first direct observation of such a parameter. The well known INADEQUATE experiment in its one-and two-dimensional versions is applied for the first time to a spin system of spin-1 nuclei. It is demonstrated that the experiment is very sensitive for the detection of 6Li,6Li spinspin interactions, and thus provides a promising alternative to the CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…0.1 M LiBr/THF) (Fig. a) and a 1D 6 Li, 6 Li INADEQUATE experiment showed a line splitting of ∆Δν = 0.50 ± 0.07 Hz that indicated homonuclear coupling between both lithium resonances (Fig. b) and proved that both lithium cations belong to the same cluster 5 2 .…”
Section: Resultsmentioning
confidence: 82%
“…0.1 M LiBr/THF) (Fig. a) and a 1D 6 Li, 6 Li INADEQUATE experiment showed a line splitting of ∆Δν = 0.50 ± 0.07 Hz that indicated homonuclear coupling between both lithium resonances (Fig. b) and proved that both lithium cations belong to the same cluster 5 2 .…”
Section: Resultsmentioning
confidence: 82%
“…The assignment of the 7 Li signals has been based on the works of F. Patéet al, 13 performed on a 6 Li-labeled solution, and confirmed by the 2D 7 Li− 7 Li COSY NMR spectrum ( Figure 1). On this spectrum, we have observed correlations between signals at δ = 2.41 ppm and δ = 2.21 ppm, between signals at δ = 2.15 ppm and δ = 1.98 ppm, and between signals at δ = 1.92 ppm and δ = 1.78 ppm, which are characteristic of the homonuclear couplings between the lithium signals belonging to the same Li 2 /Li 3 ((n-BuLi) 1 (MeLi) 3 ), Li 4 /Li 5 ((n-BuLi) 2 (MeLi) 2 ), and Li 6 /Li 7 ((n-BuLi) 3 (MeLi) 1 ) aggregate, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…8a, 9 The latter has the advantage of being more sensitive than the 2D 6 Li− 6 Li COSYLr and requires a shorter acquisition time. In the case of a system containing two coupled nuclei, the lithium signals appear in antiphase with a deviation of 2J.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(R ϭ H 81, [97] SiMe 3 82, tBu 83, 4-toloyl 84 [98] ). At low temperature, a 6 Li-enriched sample of 81 reveals two signals, with 6 Li, 6 Li INAD-EQUATE spectroscopy [99] affording a homonuclear scalar coupling and suggesting retention of the tetranuclear cocomplex noted in the solid state (see below).…”
Section: Solution Studiesmentioning
confidence: 95%